The impact of Sino-Us trade imbalance on the us economy and the trend prediction of Sino–Us trade imbalance - Shi, Jiandong (Studia Mundi – Economica, 2021)
The trade friction between China and the United States is a trade problem arising from the difference between China and the United States with regard to the balance of trade and values. As Sino–US trade develops; the trade imbalance is becoming increasingly prominent, which directly leads to the Sino–US trade war. This paper attempts to explore whether the expansion of the US–China trade deficit will result in the slowdown of the US economy and to study the development trend of Sino–US trade imbalance, emphatically discusses the impact of Sino–US trade on US GDP and establishes a model to conduct the trend prediction of Sino–US trade imbalance in the near future. The study proves that there is a two-way and long-term relationship of influence between the trend in the US–China trade deficit and in the US GDP, during which the Sino–US trade contributes to the economic growth in the United States. Meantime, the scale of Sino–US trade imbalance will still increase in the short run.
Keywords: Sino–US; trade imbalance; US economy; Cointegration analysis; Trend Prediction